PEMBERDAYAAN KESEHATAN REMAJA DENGAN PELATIHAN BANTUAN HIDUP DASAR (BHD) DI DESA BULU BALEN BOJONEGORO - Zainal Abidin, S.Kep., M.Kes., Ahmad; Khayudin, S.Kep., Ns., M.Kep., Bayu; Julianto, S.Kep., Ns., M.Kes, Errix (Jurnal Humanis ( Jurnal Pengabdian Masyarakat ISTeK ICsada Bojonegoro), 2024)
A health aspect that must be paid attention to by the public is the handling of conditions such as cardiac arrest, respiratory arrest, trauma/accidents, bites from wild and venomous animals and the like. This is also an aspect of health that every community must know well, both in terms of knowledge, causes, prevention and at least knowing how to deal with it, so that with adequate community capacity in responding to problems that occur in the surrounding environment, there will be a great opportunity to minimize the risk of death. and/or excessive disability. One of the health pillars that can be optimized is teenagers who can be trained and trained to be able to provide BHD/basic life support to these victims. With an integrated youth approach method, it is hoped that we can create a generation that is responsive to appropriate BHD management in society. The result of this community service is the creation of a generation of teenagers who are ready to respond to BHD activities with good minimum skills and have adequate cognitive abilities in accordance with their capacity in the community as the initial guard in assisting health workers in managing health and safety.